Languages and Communities in Russia in 15th to 18th Century - Komendová, Jitka (Dějiny – teorie – kritika, 2012)
The aim of the article is to extend and add detail to the cultural and social history of the Russian language presented by Peter Burke in his book Languages and Communities in Early Modern Europe. The main focus is on the dramatic linguistic controversies, which surrounded the translation of liturgical texts and the orthographic reform. These events are wholly neglected by Burke and yet, their impact on the society as a whole clearly shows that even in the context of Burke’s central emphasis on Europe-wide issues, they were far from regional or marginal. The author also finds it necessary to thoroughly reinterpret the relation between the Russian language and Church Slavonic, which Burke rather imprecisely treats as analogical to the relation between vernacular languages and Latin in the Western and Central Europe.